Analytical Essays on Music by Women Composers: Concert Music from 1960-2000 (vol. 3) – edited by Laurel Parsons and Brenda Ravenscroft (Book Review) - Prevost, Roxane (CAML Review / Revue de l’ACBM, 2018)
[no abstract]